Hubungan Frekuensi Kunjungan ke Posyandu Remaja dengan Status Gizi Remaja Putri - Friska Adila Putri Utami; Kissa Bahari; Lisa Purbawaning (NAJ Nursing Applied Journal, 2025)
Nutritional problems among adolescent girls remain relatively high and can affect reproductive health, particularly before entering marriage. One of the factors suspected to be associated with nutritional status is the frequency of visits to adolescent health posts (Posyandu Remaja). This study aimed to determine the relationship between the frequency of visits to adolescent health posts and the nutritional status of adolescent girls in the working area of Dinoyo Public Health Center. The research design employed was correlational analytic with a cross-sectional approach. The sample consisted of 80 adolescent girls registered at adolescent health posts in the Dinoyo Public Health Center area, selected using total sampling technique. Data were collected using observation sheets and analyzed using the Spearman rank correlation test. The results showed that there was no significant relationship between the frequency of visits to adolescent health posts and the nutritional status of adolescent girls (r = -0.083, p = 0.462). It can be concluded that an increased frequency of visits to adolescent health posts does not directly correlate with improvements in the nutritional status of adolescent girls in the Dinoyo Public Health Center area.